Oral and dermal exposure to natural radionuclides and heavy metals in water and sediments of Nile River, Qena, southern Egypt - Khaled Salahel Din; Faten Mahmoud (Scientific Reports, 2023)
Abstract This study assessed the levels of natural radionuclides (226Ra, 232Th, and 40K) and heavy metals (Hg, Fe, Cr, As, Zn, Cu, Cd, and Pb) in surface water and sediment samples from the Nile River in Qena Governorate, southern Egypt, using a gamma-ray spectrometer, 3ʺ NaI (Tl) scintillation detector coupled with 1024 multi-channel analyzer, and an atomic absorption spectrometer. In surface water and sediments, the average activity concentrations of natural radionuclides were 40K (4.73 Bq L−1; 395.76 Bq kg−1) > 226Ra (0.41 Bq L−1; 18.14 Bq kg−1) > 232Th (0.30 Bq L−1; 17.98 Bq kg−1). The average heavy metal concentrations in surface water in µg L−1 were Fe (121.0) > Zn (33.80) > Cr (28.0) > Cu (8.62) > Pb (8.35) > As (1.19) > Hg (0.81) > Cd (0.12). In Nile sediments the concentrations in mg kg−1 were Fe (1670.0) > Zn (207.0) > Cr (29.40) > Cu (16.20) > Pb (4.32) > Hg (0.41) > Cd (0.31) > As (0.14). The heavy metal evaluation index (HMEI) calculations for water samples revealed that 31% of the samples were suitable for domestic use, while 69% were not. The geo-accumulation index, enrichment factor, and ecological risk factor for sediments were estimated, showing extreme enrichment for Hg and Zn with high ecological risk for Hg. Health risks for adults were evaluated due to oral and dermal exposure to Nile surface water and sediments from the study area, indicating minimal radiological risks and potential carcinogenic and non-carcinogenic risks from the metals.